The production of indigenous Zebu cows under traditional smallholder management conditions in the Debre Berhan area of the Ethiopian highlands - Gautsch, K.D. (International Livestock Centre for Africa, 1987)
Reports the carcass characteristics of Menz sheep. A total of 75 male Debre Berhan Menz type sheep were slaughtered to evaluate carcass performance parameters and to identify influencing factors. Season had effect on dressing percentage due to high infestation rate with liverflukes. Includes literature review on consumer preference, meat and carcass quality characteristics and factors influencing meat production from small ruminants in sub-Saharan Africa.